SAT0194 IL-6 Serum Levels and Coronary Microvascular Dysfunction in Patients with Systemic Sclerosis. (15th July 2016) - Pigatto, E.; Famoso, G.; Scanu, A.; Polito, P.; Galozzi, P.; Zanatta, E.; Punzi, L.; Cozzi, F.; Tona, F.
Abstract : Background: Functional impairment of coronary microcirculation is thought to be a pathway in the development of cardiac involvement in systemic sclerosis (SSc). The underlying mechanism is not fully understood. A reduction of coronary flow reserve (CFR) suggests a coronary microvascular dysfunction (CMD) and predicts adverse outcomes in several cardiovascular diseases. Interleukin-6 (IL-6) is involved in the pathogenesis of SSc and it is a marker of immune activation. High serum levels of IL-6 are correlated with the severity of skin lesions, pulmonary fibrosis and pulmonary hypertension, but the role of IL-6 in the development of cardiomyopathy in SSc is yet not clear. Objectives: To assess the relationship between CFR values and IL-6 serum levels in SSc. Methods: Forty SSc patients (32 female and 8 male, aged 55±11 years), classified according to the 2013 ACR/EULAR criteria, were enrolled. Disease activity was evaluated by EUSTAR score. Twenty-three patients were affected by diffuse cutaneous form and 17 by limited form. All patients had no clinical evidence of heart disease. Coronary flow velocity in the left anterior descending coronary artery was detected by transthoracic Doppler echocardiography at rest and during adenosine infusion. CFR was the ratio of hyperaemic diastolic flow velocity (DFV) to resting DFV. A CFR ≤2.5 was considered abnormal and marker of CMD. Serum levels of IL-6 and of cardiac biomarkers (pro-BNP and troponin I) were evaluated in all patients. Results: CFR was reduced in 21 patients (52.5%). The average value was 2.08±0.29. Serum levels of IL-6 (n.v. <2.5 pg/mL), pro-BNP (n.v. <125 ng/L) and troponin I (n.v. <0.0017 μg/L) were increased respectively in 50%, 45% and 27.5% of cases. No significant correlation between CFR and subsets of SSc was found. Higher EUSTAR score were correlated with reduced CFR ( p=0.037 ) and high values of IL-6 ( p=0.002 ). A significant correlation between the increase levels of IL-6 and the reduction of CFR ( p=0.039 ) was found. Conclusions: Our results showed that high serum levels of IL-6 are associated with CMD independently from the severity of SSc. A positive correlation between IL-6, EUSTAR score and the impairment of CFR in SSc patients may be suggest an implication of IL-6 in the cardiac pathogenesis of SSc. The evaluation of serum IL-6 might represent a tool for the prediction of CMD, suggesting a role in the increased cardiovascular risk in patients with SSc. Moreover they could open new possibilities for the treatment of SSc cardiomyopathy. Disclosure of Interest: None declared